ENVIRONMENTAL DAMAGE AND EFFECTS OF CHEMICAL POLLUTANTS IN THE ATMOSPHERE ON HUMAN HEALTH CONCLUSION - Toshpulatova Munisa; Usarova Aziza; Khursanboyeva Gulchehra (Western European Studies, 2025)
Air pollution is the main concern of the newly civilized world, with serious toxicological effects on human health and the environment. It has a number of different sources of emissions, but motor vehicles and industrial processes account for a large proportion of air pollution. According to the World Health Organization, the six main air pollutants include particulate matter, ground-level ozone, carbon monoxide, sulfur oxides, nitrogen oxides, and lead. Long- and short-term exposure to airborne toxins has a variety of toxicological effects on humans, including respiratory and cardiovascular diseases, neuropsychiatric complications, eye irritation, skin disorders, and long-term chronic illnesses such as cancer. Several reports have found a direct correlation between poor air quality and increased morbidity and mortality rates, mainly due to cardiovascular and respiratory diseases. Air pollution is a major environmental risk factor in the prevalence and development of certain diseases such as asthma, lung cancer, ventricular hypertrophy, Alzheimer's and Parkinson's diseases, psychological complications, autism, retinopathy, fetal growth and low birth weight
Keywords: toxicology; ground-level ozone; carbon monoxide